2009
DOI: 10.1017/s0376892909990373
|View full text |Cite
|
Sign up to set email alerts
|

Deforestation and conservation in major watersheds of the Brazilian Amazon

Abstract: SUMMARYConserving natural vegetation cover is of critical importance for maintaining the ecological integrity and hydrological properties of large river basins (more than 100 000 km 2 ). Recent estimates indicate that more than 700 000 km

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
6

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 39 publications
0
36
0
6
Order By: Relevance
“…However, these two indicators were considered important in the semi-arid region Brazil based on the fact that the region has relatively low development indexes and several inadequate land uses practices, and previous studies in other regions of Brazil (Trancoso et al, 2010) have shown that conservation enforcement in protected areas is crucial for avoiding degradation.…”
Section: Resultsmentioning
confidence: 99%
“…However, these two indicators were considered important in the semi-arid region Brazil based on the fact that the region has relatively low development indexes and several inadequate land uses practices, and previous studies in other regions of Brazil (Trancoso et al, 2010) have shown that conservation enforcement in protected areas is crucial for avoiding degradation.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, some studies report that even larger changes in forest coverage (greater than 33%) may not cause changes to the streamflow regime. For example, no flow variation trends were observed (Trancoso et al, 2007) in large watersheds distributed in the Madeira, Tapajós and Xingu rivers watersheds, or even in those where more than half of the area is deforested (Trancoso et al, 2009). These data seem to indicate that changes in the FC alone may not be sufficient to affect the streamflow, although other factors also influence the hydrological behavior of watersheds.…”
Section: Relationship Of the Streamflow With Forest Coverage And Precmentioning
confidence: 96%
“…However, although large areas have already been deforested in the Amazon River Basin, the balance between deforestation and conservation is still positive from the perspective of ecological processes and conservation [51]. On the scale of large watersheds, the area delimited by conservation areas is more than three times larger than the deforested areas [51]. These conservation measures might improve the status of wetland ecosystem health.…”
Section: Discussionmentioning
confidence: 99%